Health literacy and long-term health outcomes following myocardial infarction: protocol for a multicentre, prospective cohort study (ENHEARTEN study). Issue 5 (6th May 2022) - Beauchamp, Alison; Talevski, Jason; Nicholls, Stephen J; Wong Shee, Anna; Martin, Catherine; Van Gaal, William; Oqueli, Ernesto; Ananthapavan, Jaithri; Sharma, Laveena; O'Neil, Adrienne; Brennan-Olsen, Sharon Lee; Jessup, Rebecca Leigh
Abstract : Introduction: Low health literacy is common in people with cardiovascular disease and may be one factor that affects an individual's ability to maintain secondary prevention health behaviours following myocardial infarction (MI). However, little is known about the association between health literacy and longer-term health outcomes in people with MI. The ENhancing HEAlth literacy in secondary pRevenTion of cardiac evENts (ENHEARTEN) study aims to examine the relationship between health literacy and a number of health outcomes (including healthcare costs) in a cohort of patients following their first MI. Findings may provide evidence for the significance of health literacy as a predictor of long-term cardiac outcomes. Methods and analysis: ENHEARTEN is a multicentre, prospective observational study in a convenience sample of adults (aged > 18 years) with their first MI. A total of 450 patients will be recruited over 2 years across two metropolitan health services and one rural/regional health service in Victoria, Australia. The primary outcome of this study will be all-cause, unplanned hospital admissions within 6 months of index admission. Secondary outcomes include cardiac-related hospital admissions up to 24 months post-MI, emergency department presentations, health-related quality of life, mortality, cardiac rehabilitation attendance and healthcare costs. Health literacy will be observed as a predictor variable and will be determined using the 12-item version of the European Health Literacy Survey (HLS-Q12). Ethics and dissemination: Ethics approval for this study has been received from the relevant human research ethics committee (HREC) at each of the participating health services (lead site Monash Health HREC; approval number: RES-21-0000-242A) and Services Australia HREC (reference number: RMS1672). Informed written consent will be sought from all participants. Study results will be published in peer-reviewed journals and collated in reports for participating health services and participants. Trial registration number: ACTRN12621001224819.